High Performance Ultra Low-k (k=2.0/keff=2.4)/Cu Dual-Damascene Interconnect Technology with Self-Formed MnSixOy Barrier Layer for 32 nm-node - Usui, T.; Tsumura, K.; Nasu, H.; Hayashi, Y.; Minamihaba, G.; Toyoda, H.; Sawada, H.; Ito, S.; Miyajima, H.; Watanabe, K.; Shimada, M.; Kojima, A.; et al. (Proceedings of the IEEE International Interconnect Technology Conference, 2006)
In order to realize the effective dielectric constant (k eff)=2.4 for 32 nm-node copper (Cu) dual-damascene (DD) interconnects, a spin-on-dielectric (SOD) SiOC (k=2.0) as the inter-level dielectric and plasma-induced damage restoration treatment were successfully demonstrated. It was obtained that good via resistance and stress-induced voiding (SiV) reliability. In addition, CoW-cap and thin SiC (k=3.5) and dual hard mask process using a metal layer was proposed to reduce the capacitance of dielectric diffusion barrier and protection layers in hybrid (PAr/SiOC) inter-layer dielectric (ILD) structure. As for the metallization, a self-formed MnSi x O y barrier technology was applied in hybrid ILD structure. Drastic reduction of via resistance and excellent electromigration and SiV performance were obtained for the first time in hybrid ILD structure